Processamento viscoplástico e conformação cerâmica por rolos a frio a partir de suspensões concentradas de alumina - Pardo, Arturo Rodrigo Ferreira (2005)
Plastic forming, followed by roll-pressing, allows to shape ceramic bodies with thickness that are useful for electronic and pavement ceramics. This work introduces an alternative route to processing ceramic plastic mixes. The first step comprehended the selection of suitable raw materials with the aim of assure the best packing of particles, followed by decreased porosity and water consumption. Theoretical porosity of distinct calcined alumina was calculated with data obtained by measuring some properties of the raw materials: density (picnometry), specific surface area and particle size determination by the sedimentation technique. Deflocculants with distinct molecular design and plasticizer adequate to the route proposed were selected. The proposed route involved processing a ceramic suspension as most concentrated as possible with pseudo plastic rheological behavior. This behavior was determined by viscosimetry of the suspension. Alumina plastic mix was processed by mixing an alumina suspension using a mechanical mixer, followed by adding the plasticizer with a helix mixer and finally became homogeneous by knife milling. Drying and firing settings were chosen with the aim of avoid thermal stresses that would damage the ceramic bodies. Rheological behavior of plastic mixes was also measured. Physical, mechanical and microestrutural characteristics of the ceramic bodies were also measured after roll forming. The influence of some processing parameters was also evaluated: roll velocity, thickness of the ceramic bodies and de-airing of plastic mix. Results allowed deducing that viscoplastic processing is an interesting alternative, low cost one, of forming ceramic substrates with low water (12% wt) and organic additive (2% wt) content.